Identification of Microplastic Composition on Clams (Gafrarium tumidum) and Sediments in Seribu Island, Pari Island Area, DKI Jakarta - Winesti Tubagus; Sunarto Sunarto; Mochamad Rudyansyah Ismail; Lintang Permata Sari Yuliadi (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2020)
Microplastic is one of the pollutants that can contaminate marine biota even spread in sea waters and coastal substrate because of the sizes ranges to 10 μm - 2 mm. This pollutant is spread in marine waters and found in the area of Seribu Island, Pari Island Area, DKI Jakarta. This research aims to identify the amount of abundance, type, size, and color of microplastic that was found in sediment and shell samples. The research method used was a survey method and laboratory analysis. The method consists of three parts, namely field data collection, identification using a microscope, and describing the results of identification.  All sediment and shell samples were identified as being contaminated with microplastics. Microplastic are found in fiber, fragment, and film type. That color found including black, yellow, red, blue, green, chocolate, and clear. The most dominant microplastic color is black and the most dominant microplastic size is the small size group. The highest microplastic abundance in sediment samples from 3 stations is found in samples taken by station 2 with an average of 43.67 particles. 100 g-1 of dry sediment and the most dominant type is the fiber type from all sediment samples. The most dominant type of mussels sample is fragment type and the average abundance of microplastics in the highest sample of mussels is worth 17.33 particles.ind-1.